Addition of Wendler Glottoplasty to Voice Therapy Improves Trans Female Voice Outcomes. (26th August 2020) - Brown, Sarah K.; Chang, Joseph; Hu, Shirley; Sivakumar, Ganesh; Sataluri, Medha; Goldberg, Leanne; Courey, Mark S.
Abstract : Objectives/Hypothesis: VT is often considered the preferred treatment for vocal feminization in transgender patients. However, Wendler glottoplasty offers a surgical option for increasing fundamental frequency and perception of vocal femininity. We aimed to determine whether the addition of glottoplasty to VT results in greater fundamental frequency elevation and improvement in quality‐of‐life measures. Study Design: Retrospective case series. Methods: Forty‐eight trans female patients were treated for vocal feminization. Twenty‐seven patients underwent VT, and 21 patients underwent VT with additional glottoplasty (VTWG). Pre‐ and posttreatment acoustic measures, Trans Woman Voice Questionnaire (TWVQ), and Voice Handicap Index‐10 (VHI‐10) data were compared. Results: Glottoplasty in combination with VT elevated average speaking fundamental frequency (SF0) to a greater extent than VT alone ( P  < .0001). The VTWG group achieved a 42‐Hz increase in SF0, whereas the VT group achieved a 15‐Hz increase in SF0. In both the VT and VTWG groups, the lower bound of physiologic range increased by 18 Hz ( P  = .0008 and P  = .016, respectively). The addition of glottoplasty also resulted in greater improvement in voice‐related quality of life. Improvement in TWVQ and VHI‐10 was significantly greater in the VTWG group than the VT group ( P  = .007 and P  = .029, respectively). TWVQ showed statistically significant improvement in the VTWG group only. Conclusions: VT results in SF0 elevation and improvement in VHI‐10. The addition of glottoplasty to VT results in further improvements in SF0 and VHI‐10 and statistically significant improvement in TWVQ. Level of Evidence: 4 Laryngoscope, 131:1588–1593, 2021